Analisis Abnormal Return, Trading Volume Activity Dan Market Capitalization Sebelum Dan Sesudah Vaksinasi Pasar Sebelum Dan Sesudah Vaksinasi Covid-19 Pada Sektor Infrastruktur - Devina Agrivina; Esi Fitriani Komara (Universitas Sultan Ageng Tirtayasa, 2022)
The results of this study include an event study that intends to analyse the conditions and differences in abnormal returns,trading volume activity and market capitalization before and after the first Covid-19 vaccination in Indonesia in the infrastructure sector on the Indonesia Stock Exchange.In this study,a sample of 20 companies in the infrastructure sector was used.This study uses a research period of 4 days before the event,1 day at the time of the event and 4 days after the event.The research uses descriptive statistical techniques,normalitiy test (Shapiro-Wilk statistic test),one sample Kolmogorov-Smirnov abnormal returns test and Wilcoxon signed rank test.The results indicate abnormal returns,trading volume activity and market capitalization the data are not normally distributed,the result indicate that there is an abnormal return around vaccination Covid-19,the resut indicate no differences in abnormal return and market capitalization,but there are differences in trading volume activity before and after vaccination Covid-19 in infrastructure sector.